Application and Characterization of Surfactants 2017
DOI: 10.5772/68020
|View full text |Cite
|
Sign up to set email alerts
|

The Versatile Dioctadecyldimethylammonium Bromide

Abstract: Dioctadecyldimethylammonium bromide (DODAB) is a quaternary ammonium surfactant (Quat) with interesting properties and applications. In this chapter, DODAB characteristics as compared to other Quats emphasize its self-assembly in aqueous solutions and the novel applications involving this useful cationic lipid so easily combined with biomolecules and interfaces to yield a wide range of novel uses in many fields such as delivery of drugs, vaccines and genes, design of nanoparticles, modification of interfaces, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 115 publications
(187 reference statements)
0
28
0
Order By: Relevance
“…Such kind of nanoformulations was recommended for topical therapy [68]. Cationic surfactants with double, long-chains exhibited antimicrobial properties [69]. It was confirmed that the determining factor of the antifungal action of cationic surfactants is not cell lysis, but a change in the cell surface from negative to positive charge [70].…”
Section: Antimicrobial Activity and Hemolysis Of Dhdhabmentioning
confidence: 91%
“…Such kind of nanoformulations was recommended for topical therapy [68]. Cationic surfactants with double, long-chains exhibited antimicrobial properties [69]. It was confirmed that the determining factor of the antifungal action of cationic surfactants is not cell lysis, but a change in the cell surface from negative to positive charge [70].…”
Section: Antimicrobial Activity and Hemolysis Of Dhdhabmentioning
confidence: 91%
“…In summary, cationic micro and nanoparticles are effectively taken up both by macrophages and dendritic cells since electrostatic attraction promotes particle binding and subsequent internalization [11,14,20,24,25]. Cationic particles and liposomes containing dioctadecyldimethylammonium bromide (DODAB) cationic lipid [13,26] carrying Mycobacterium tuberculosis [13,27], Chlamydia trachomatis [11], or Neisseria meningitides antigens enhanced the cellular and humoral immune response against them [16,28].Another important class of cationic adjuvants is represented by the cationic polymers despite their overt cytotoxicity [29][30][31][32][33]. They easily combine with oppositely charged proteins [34].…”
mentioning
confidence: 99%
“…In the absence of PMMA, QACs in water dispersion self-assemble to yield micelles or bilayers depending on the QAC chemical structure and molecular shape [32,33]. Dioctadecyl dimethyl ammonium bromide (DODAB) assembles in water solution as bilayer vesicles or bilayer fragments (BF) depending on the dispersion method; sonication disrupts DODAB vesicles producing BF [34][35][36]. Cetyltrimethylammonium bromide (CTAB) assembles in water solution as micelles above the critical micellar concentration [32].…”
Section: Introductionmentioning
confidence: 99%